DUAL-CHANNEL SUPPLY CHAIN MODEL BASED ON TIME TRANSACTION OF DEALING BY NOTICE DISRUPTION RISK FACTOR - Slamet Krismanto; Ririn Setiyowati; Sutanto Sutanto (Universitas Ahmad Dahlan, 2020)
The fourth industrial revolution era requires an effectiveness and efficiency to enforce the industrial activities, one of them, such as minimization of transaction time of dealing that consists of service and delivery time. The purpose of this research is to calculate the industrial profit using dual-channel supply chain model based on the transaction time of dealing by notice disruption risk factor on retailers as the effect of mindset changing of consumers. In this research, we construct the maximization model of profit in the system between manufacture and multi-retailer. Multi-retailer's economical activities have some disruption risk factors on the retail engagement. Furthermore, we determine the optimum solution using Newton method so we get the optimum profit of the system is 620372. That kind of situation is reached when the offered price of manufacturer, retailer 1, and retailer 2 is 318.99, 352.48, and 345.43 respectively with the probability of disruption is 9.15%. Depend on sensitivity analysis of profit system, the profit increase significantly to 1010948. It occur when priority of consumers demand to retailer 1 is missing to 9.3 units per price changing of retailer 2.